Designing a Multichannel Map Service Concept - Halkosaari, Hanna; Sarjakoski, Tiina; Ylirisku, Salu; Sarjakoski, Tapani (Human Technology, 2013)
This paper introduces a user-centered design process for developing a multichannel map service. The aim of the service is to provide hikers with interactive maps through several channels. In a multichannel map service, the same spatial information is available through various channels, such as printed maps, Web maps, mobile maps, and other interactive media. When properly networked, the channels share a uniform identity so that the user experiences the different channels as a part of a single map service. The traditional methods of user-centered design, such as design probes, personas, and scenarios, proved useful even in the emerging field of developing multichannel map services. The findings emphasize the need to involve users and multidisciplinary teams in the conceptual phases of designing complex services aimed at serving various kinds of users.